2013
DOI: 10.1530/joe-13-0144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity and estradiol on Na+/K+-ATPase and their relevance to cardiovascular diseases

Abstract: Obesity is associated with aberrant sodium/potassium-ATPase (Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 123 publications
2
13
0
1
Order By: Relevance
“…So the enzyme in 24 weeks old female rats probably extrudes better the excessive sodium ions as compared to respective male groups. This effect may be ascribed to estradiol because several previous studies have shown that this hormone is one of the primary Na, K-ATPase regulators increasing the activity/expression of the enzyme in the cardiovascular system [36][37][38][39][40]. The above hypothesis is supported also by our Western blot data which indicate higher expression of a3 subunit in healthy females and also in female rats subjected to subchronic as well as to chronic diabetes.…”
Section: Discussionsupporting
confidence: 85%
“…So the enzyme in 24 weeks old female rats probably extrudes better the excessive sodium ions as compared to respective male groups. This effect may be ascribed to estradiol because several previous studies have shown that this hormone is one of the primary Na, K-ATPase regulators increasing the activity/expression of the enzyme in the cardiovascular system [36][37][38][39][40]. The above hypothesis is supported also by our Western blot data which indicate higher expression of a3 subunit in healthy females and also in female rats subjected to subchronic as well as to chronic diabetes.…”
Section: Discussionsupporting
confidence: 85%
“…The metabolic mechanisms associated with weight gain include insulin resistance often accompanied by hyperinsulinemia, impaired glucose tolerance, and eventually type 2 diabetes as well as atherogenic dyslipoproteinemias, fatty liver disease, prolonged QT interval (89), myocardial fatty infiltration with impaired myocardial energetic efficiency (147), and increased thrombogenesis (169). In addition, obesity-related hypoventilation syndromes (e.g., chronic hypercapnia and obstructive sleep apnea) have been associated with increased cardiovascular morbidity and mortality (150).…”
Section: Effect Of Sustained Weight Loss On Major Cardiovascular Disementioning
confidence: 99%
“…NDRG2 is a cytoplasmic protein and member of the NDRG family that belongs to the α/β hydrolase family and is known as a tumor suppressor gene (MA et al, 2012;OBRADOVIC et al, 2013;. NDRG2 is a target gene of E2 through binding to ERβ, which in turn regulates its expression via transcriptional activation , reinforcing our TFBS data: on day 60 p.o.…”
supporting
confidence: 81%
“…NKA is responsible for creating an electrochemical gradient across the plasma membrane, but exerts other functions like cell adhesion, motility and signal transduction (OBRADOVIC Et al., 2013;CHEN et al, 2014;LANGHANS, 2015). In porcine preovulatory luteinized follicles, ATP1A1 was functionally classified as a cell growth inhibitor (AGCA et al, 2006).…”
mentioning
confidence: 99%